City i-Tick: The android based mobile application for students’ attendance at a university - S. R. Alimin; N. H. Abdul Hamid; Z. A. Nasruddin (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents City i-Tick, the android based mobile application for students’ attendance at a university. In this study, we developed mobile application for lecturers to take students’ attendance in City University, Petaling Jaya. Managing students’ attendance during lecture periods has become a difficult challenge. The research objectives for this study are to identify user requirement for City i-Tick, to design and develop City i-Tick, and to demonstrate the prototype of City i-Tick. The study is a narrative participatory design and exploits Design Thinking as the research methodology. City i-Tick was successfully validated by 14 lecturers and System Usability Scale (SUS) was used to determine the findings of the study. We found that City i-Tick is effective for lecturers in taking attendance because it is easy to use, easy to learn, and the users feel confident when using this application.